2023
DOI: 10.3390/pathogens12070957
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogens and Parasitoids Allied in Biocontrol: A Systematic Review

Abstract: Biological pest control is an environmentally friendly alternative to synthetic pesticides, using organisms such as viruses, bacteria, fungi, and parasitoids. However, efficacy is variable and combining different biocontrol agents could improve success rates. We conducted a systematic review of studies combining a parasitoid with an entomopathogenic microorganism, the first of its kind. We searched in Web of Science and extracted data from 49 publications matching the pre-defined inclusion criteria. Combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Previous research has suggested that the susceptibility of the aphid endoparasitoid Aphidius colemani to B. bassiana is high in laboratory settings, whereas lower infection rates are observed in greenhouse environments, likely due to complex environmental conditions [37]. Additionally, more studies have reported an additive effect rather than a reduced effect when these two biocontrol agents are combined [38,39]. Our results demonstrate that a spray of four conidia/mm 2 or the ingestion of 3 × 10 4 conidial/mL has an adverse effect on the survival rates of adult wasps.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that the susceptibility of the aphid endoparasitoid Aphidius colemani to B. bassiana is high in laboratory settings, whereas lower infection rates are observed in greenhouse environments, likely due to complex environmental conditions [37]. Additionally, more studies have reported an additive effect rather than a reduced effect when these two biocontrol agents are combined [38,39]. Our results demonstrate that a spray of four conidia/mm 2 or the ingestion of 3 × 10 4 conidial/mL has an adverse effect on the survival rates of adult wasps.…”
Section: Discussionmentioning
confidence: 99%
“…But the adverse influences were slight [ 27 ]. Some species of beneficial insects have even been used to spread entomopathogenic fungi in some studies [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in microbial insect pathogens stems, in part, from their potential as biological agents that can be used as alternatives to chemical pesticides due to their lower environmental toxicity and decreased off-target effects [ 1 , 2 , 3 ]. Examining naturally occurring enzootic diseases, particularly of insect pests, is important for increasing our understanding of basic ecological processes, but it also represents a reservoir for the discovery of locally adapted biological agents that could potentially be exploited for pest control [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%